Ulasan Artikel: Islamic Legal Theory Curriculum: Are The Classical Taught Today? Oleh Monique C. Cardinal Di Dalam Islamic Law And Society 2005 -12(2): 224-272. - Buang, Ahmad Hidayat (Jurnal Fiqh, 2019)
Article Review: Islamic Legal Theory Curriculum: Are the Classical Taught Today? Oleh Monique C. Cardinal di dalam Islamic Law and Society 2005 -12(2): 224-272.